Buying In or Dropping Out: The Public Policy Implications of Social Cohesion Research - Jeannotte, M. Sharon; Stanley, Dick; Pendakur, Ravi; Jamieson, Bruce; Williams, Maureen; Aizlewood, Amanda (Université d'Ottawa | University of Ottawa, 2002)
This paper is intended as a “primer” on the subject of social cohesion and as a summary of what we know about it so far. In it, we describe the framework for Canadian research on this topic, outline our research findings, draw tentative conclusions from those findings and suggest possible next steps for our research.
Keywords: Social cohesion